E-002 Middle cerebral artery pressure changes following pipeline flow diversion. (23rd July 2017) - Brunozzi, D; Shakur, S; Charbel, F; Alaraj, A
Abstract : Introduction: Pipeline embolization devices (PED) are commonly used for endovascular treatment of cerebral aneurysms but can be associated with delayed ipsilateral intraparenchymal hemorrhage. Changes in intracranial hemodynamics after PED deployment are poorly understood. Here, we assess middle cerebral artery (MCA) pressure before and after PED treatment. Methods: Records of patients with cerebral aneurysms proximal to internal carotid artery terminus treated with PED at our institution between 2015–2017 were retrospectively reviewed. Ipsilateral MCA pressure was recorded before and after PED deployment. Systemic blood pressure was also simultaneously recorded. MCA pressure and ratio of MCA to systemic blood pressure were compared before and after treatment using the paired student t test. Results: 11 patients were included. Mean age was 48 years. Systolic, diastolic, and mean MCA pressures did not significantly change after PED (90.1 vs. 86.2 mmHg, p=0.25; 66.3 vs. 64.0 mmHg, p=0.38; 75.8 vs. 74.2 mmHg, p=0.44). However, ratio of systolic MCA to systolic systemic pressure was significantly higher after treatment (0.77 vs. 0.71, p=0.05, fig A), and ratio of diastolic and mean MCA to diastolic and mean systemic pressures tended to increase after PED (1.06 vs. 1.01, p=0.11; 0.93 vs. 0.89, p=0.08). Conclusion: Following PED deployment, the ratio of systolic MCA to systemic pressure increased significantly, indicating possible disruption of cerebral autoregulation. Further study may reveal that these altered hemodynamics are responsible for delayed ipsilateral intraparenchymal hemorrhage after PED. Disclosures: D. Brunozzi: None. S. Shakur: None. F. Charbel: 2; C; Transonic. 4; C; Ownership VasSol Inc. A. Alaraj: 1; C; NIH. 2; C; Codman-Cordis.